Mechanical behavior of designed AH32 steel specimens under tensile loading at low temperatures: Strength and failure assessments based on experimentally verified FE modeling and analysis - Arfandi Ahzhan Muhammad Fauzan; Suryanto Suryanto; Prabowo Aditya Rio; Muttaqie Teguh; Do Quang Thang; Santoso Budi; Laksono Fajar Budi; Nubli Haris (Journal of the Mechanical Behavior of Materials)
This research investigates the mechanical behavior and performance of AH32 steel when subjected to low temperatures, particularly in the context of ship hull structures operating in cryogenic environments. The study uses experimental procedures and advanced numerical simulations through ABAQUS CAE to evaluate vital mechanical properties such as Young’s modulus, yield stress, ultimate tensile strength, and fracture toughness across temperatures ranging from 20 to −160°C. The results reveal a consistent trend of increasing strength and decreasing ductility at lower temperatures, with validation achieved through an error margin of less than 10%. The findings underscore the material’s suitability for cryogenic applications but highlight the potential for brittle fracture, necessitating careful design considerations in Arctic or liquefied natural gas transport conditions. However, the study is limited to specific geometric configurations and loading conditions, suggesting that future research should explore additional geometries, fatigue behavior, and long-term performance under varying environmental conditions to assess the material’s viability in extreme environments fully.